A Tale of Two Pandemics: Antimicrobial Resistance Patterns of Enterococcus spp. in COVID-19 Era - Dan Alexandru Toc; Alexandru Botan; Ana Maria Cristia Botescu; Vlad Dumitru Brata; Ioana Alina Colosi; Carmen Costache; Lia Monica Junie (MDPI AG, 2023)
Although the COVID-19 pandemic has held the spotlight over the past years, the antimicrobial resistance (AMR) phenomenon continues to develop in an alarming manner. The lack of strict antibiotic regulation added to the overuse of antimicrobials fueled the AMR pandemic. This paper aims to analyze and identify the impact of the COVID-19 pandemic on antibiotic resistance patterns of Enterococcus spp. The study was designed as a retrospective observational study. Enterococcus spp. infections data were collected from one academic hospital in Cluj-Napoca, Romania over 18 months. A statistical analysis was performed to compare antibiotic resistance phenotypes identified. We recorded an increase in the isolation rates of Enterococcus spp. strains, from 26 isolates (26.53%) during Period A (November 2020-April 2021) to 42 strains (42.85%) during Period C (November 2021-April 2022). The number of strains with resistance to vancomycin increased from 8 during Period A to 17 during Period C. Of the total 36 strains with resistance to vancomycin, 25 were identified as E. faecium. SARS-CoV-2 patients (n = 29) proved to be at risk to develop an E. faecium co-infection (n = 18). We observed that strains with resistance to ampicillin (n = 20) and vancomycin (n = 15) are more often isolated from these patients. All changes identified in our study are to be considered in the light of COVID-19 pandemic, highlighting the threatening AMR phenomenon in Romania. Further studies should be performed to quantify the worldwide effects of these pandemics.